Avaliação da eficiência da técnica de obturação pela compressão hidráulica vertical após instrumentação automatizada - Marinho, Jovanka última (2008)
The purpose of this study was to evaluate through radiographic and microscopic analysis the efficiency of the filling techniques by vertical hidraulic compression after the root canal mechanical instrumentation in vitro as well to evaluate the marginal apical leakage through macroscopic and microscopic analysis. Thirty human mandibular molars were used , they were divided on three groups, these were subdivided on six subgroups with five specimens each, come down to 106 root canals filled. Initially, the teeth were instrumented with Profile system series 29 and filled with two ways: single accessory cone or single cone associated with gutta-percha secundary cone, with Fill Canal sealer or Sealer 26. Completed the filling, the teeth were coated with araldit and finger -nail polish except for the apical 2 mm and dried for 3 hours, thep radiographs were taken of the teeth in orto and disto-radiai directions. Next, the coronal seal was carried out with composite resin photopolymerized and with their process of making impermeable. Teeth of positive controls were used without araldit and finger-nail polish whereas the negative controls were used with total coat of araldit and finger-nail polish. The specimens were placed in 2% Methylene Blue dye for 24 hours and thermocycled for 7 days. Afterwards, sections were made of each tooth at mesial and distal roat, after this the teeth were radiographed at buccolíngual direction for a macroscopic analysis and at buccolingual and mesiodistal directions for assessment of the marginal apical leakage. Cross sections were made 3 mm to 3mm since the tooth apice. The sections obtained for each group were observed with a stereomicroscope to evaluate the quality of the root canal filling and the marginal apical leakage. The results showed that: In the four techniques the marginal dye leakage was present in the apical third; in all groups the quality of the root canal filling in the radiography was better at mesial root canal and the single cone technique showed inefficient when only a single distal root canal was present. In the radiographic evaluation the best quality of the root canal filling was observed in the 1A group (single accessory cone + FiIl Canal), as in the mesial root as in the distal root wich Shcwed twe root canals: when the distaI root had only one canal. the best result was showed by 28 group (single accessory cone associated with secundary cone + Fill Canal) In the macroscopic analysis of longitudinal !eaKage (outside surface). less leakage was showed as In the mesial root as in the distal root in the negative control group (3) followed 2A group (single accessory cone + Sealer 26). When the microscopic analysis of tranversal leakage of both roots (inside surface) was carried out. the groups that showed less dye leakage were the negative control (38) followed the 28 group (single acessory cone associated with secundary cone + Sealer 26). The homogeneity o filling was best noted in the 1 A group (.single accessoty cone + Fill Canal). The groups that showed less dye penetration in the tranversal leakage (total area) were negative control (3B) and 2B